Euclid and geometry - DeLacy, Estelle A. frey50 (Franklin Watts New York, 1963)
A history of Euclid and the developement of Euclidean geometry in Greece the time of Plato.
Keywords: Euclid -- Greece -- Geometry -- Euclidean geometry; History